The Roles of Carbohydrate-Electrolyte Solutions in Athlete Hydration Status and Performance : A Narrative Review - Ervira Wahyuni; Diana Sunardi; Bernie Endyarni Medise (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Dehydration is prevalent among athletes. Dehydration may cause fluid and electrolyte imbalance and impairment of an athlete physical and cognitive performance. Carbohydrate electrolyte solutions (CES) are often used by athletes as a rehydration fluid because it is claimed to have numerous beneficial effects on hydration status and performance. Studies on the use of carbohydrate-electrolyte solutions showed mixed results. Some studies also highlighted the side effects of carbohydrate-electrolyte solutions on gastrointestinal system. This review aimed to summarize the roles of carbohydrate-electrolyte solutions on hydration status and performance of athletes. The literature review was conducted in the narrative type. Database search was conducted using Pubmed Central search engine. The search terms used were "carbohydrate", "electrolyte", "athlete", "hydration", and "performance". The results show that carbohydrate-electrolyte solutions may prevent dehydration and electrolyte disturbance by increasing water absorptions and retentions. The maintenance of hydration status and the ergogenic effect exerted by carbohydrate can also prevent performance deteriorations. The formulation and administration of carbohydrate-electrolyte solutions must be done with caution and be given at the right timing to reduce side effects, primarily the gastrointestinal discomfort.